P-281 A multi-centre evaluation of a novel 4-cell embryo classification system based on intercellular contact points. (30th June 2022) - Hariharan, R; He, P; Karpavičiūtė, N; Derrick, R; Jacques, C; Chambost, J; Ebner, T; Rosselot, M; Loubersac, S; Wouters, K; Zaninovic, N; Miller, R; et al.
Abstract: Study question: Is there any prognostic value to classifying 4-cell embryos according to intercellular contact points (ICPs)? Summary answer: A significant association was found between the new blastomere arrangement classifications and blastulation, as well as blastocyst quality. No significant association was found for pregnancy. What is known already: Current literature states that the geometric arrangement of blastomeres in 4-cell embryos is usually classified as either "tetrahedral" or "non-tetrahedral/planar". Though tetrahedral embryos have been associated with greater developmental capacity, their prevalence has varied between studies. At ESHRE 2021, Hickman et al . proposed a more fine-grained classification system; each class was associated with a 4-digit code, where the Nth digit in said code gave the number of cells with N-1 ICPs. This gave rise to 6 classes: tetrahedral (0004), pseudotetrahedral (0022), planar (0040), closed-Y (0121), open-Y (0301) and linear (0220). In our study, we evaluate this new system. Study design, size, duration: This study was a retrospective analysis of 844 4-cell embryos across 3 clinics in 3 countries. Focal stacks of the embryos were captured on Embryoscope/MIRI time-lapse incubators between 2018 and 2020. Embryos were annotated by their respective clinics using the original "tetrahedral/planar" system. Additionally, data on blastulation, blastocyst grade (Gardner scale) and biochemical pregnancy rates were obtained for each embryo. Participants/materials, setting, methods: The embryos were annotated according to the new system by a panel of three researchers without knowledge of the clinics' or each other's classifications. Afterwards, the panelists assembled for discussion and a unanimous consensus was reached for each embryo. The cell arrangement classes were analysed with respect to blastulation rates, blastocyst grade and pregnancy rates using chi-squared tests. The distribution of classes across the clinics was also analysed, as well as agreement among the panelists. Main results and the role of chance: Under the new system, tetrahedral and pseudotetrahedral embryos saw significantly higher rates of blastulation (P = 0.017) and good-quality blastocysts (p = 0.043; here, "good-quality" means that the grade contains no 'C's or numbers less than 3) compared to other arrangements. No association was found with respect to biochemical pregnancy (p = 0.77). There was significant variation between the clinic-provided classifications (p < 0.001) with tetrahedral-to-planar ratios ranging from 1 to 9. Under the new system, there was no significant difference between the proportions of each arrangement (p = 0.66). The arrangements in order of decreasing prevalence across all the data were tetrahedral (63.7%), pseudotetrahedral (25.8%), planar (8.0%), closed-Y (2.2%) and linear (0.3%). No open-Y embryos were observed. Upon comparison with the clinic-provided tetrahedral/planar classifications, there were clear differences in the treatment of pseudotetrahedral embryos - some clinics predominantly classified them as "tetrahedral" while others as "planar". Prior to any discussions, the panelists' annotations unanimously agreed on the classifications of 63% of the embryos; with 33% of the embryos having 2 different classifications and 4% of embryos causing total disagreement. The majority of disagreements regarded pseudotetrahedral embryos being confused for either tetrahedral or planar embryos. Limitations, reasons for caution: It can be at times difficult to visualise the 3D structure of embryos from focal stacks. As a result, some annotations may be erroneous, though the use of a panel-based approach helped to mitigate this. Moreover, further studies will need to take place to validate the findings in this work. Wider implications of the findings: The findings demonstrate the prognostic utility of Hickman et al .'s ICP-based classification system. Moreover, the findings suggest that much of the variability seen in the prevalence of tetrahedral embryos under the tetrahedral/planar system came from the mislabelling of pseudotetrahedral embryos which comprised 25.8% of the study population. Trial registration number: N/A